Total acid number reduction kinetics of naphthenic acids using non-catalytic subcritical methanol - Zafar, F.; Mandal, P.C.; Shaari, K.Z.B.K.; Nadeem, S. (American Institute of Physics Inc., 2017)
Naphthenic acids (NAs) are weak organic acids present in the heavy crude oil and Oil Sand Bitumens. Whereas, the NAs are the major cause of corrosion in different processing, handling and storage equipment's of the refinery. Esterification of these acids can be an interesting method to reduce the NAs content in the crude oil besides its esters are valuable commodity and can be used as added lubricant in the oils. In this study, NAs reduction kinetics were investigated in a batch type reactor with subcritical methanol, the experiments were performed at temperatures of 150-210°C and fixed methanol partial pressure of 2 MPa. Findings of this study demonstrate that the 59 of total acid number (TAN) reduction was achieved at the temperature of 210°C, methanol partial pressure of 2 MPa and reaction time of 150 min. The TAN reduction followed second order kinetics with activation energy and frequency factor of 54.15 KJ/mol and 7.6×103, respectively. These results suggest that subcritical methanol can be an effective to reduce the TAN non-catalytically. © 2017 Author(s).